2021
DOI: 10.3390/molecules26185558
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects and Mechanisms of Procyanidins on Parkinson’s Disease In Vivo and In Vitro

Abstract: This research assessed the molecular mechanism of procyanidins (PCs) against neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and its metabolite 1-methyl-4-phenylpyridinium (MPP+) induced Parkinson’s disease (PD) models. In vitro, PC12 cells were incubated with PCs or deprenyl for 24 h, and then exposed to 1.5 mM MPP+ for 24 h. In vivo, zebrafish larvae (AB strain) 3 days post-fertilization (dpf) were incubated with deprenyl or PCs in 400 μM MPTP for 4 days. Compared with MPP+/MPTP alone, PCs sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Nuclear factor-erythroid 2-related factor 2 (Nrf2) is released from Keap1 after ROS activation. It will bind to the nucleus's antioxidant response element (ARE), and increased the expression of peroxidase, such as heme oxygenase-1 (HO-1), glutamate-cysteine ligase catalase (GCLC), glutamate-cysteine ligase (GCLM), and quinone oxidoreductase 1 (NQO1) [22]. ACR treatment could also altered the expression of Nrf2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor-erythroid 2-related factor 2 (Nrf2) is released from Keap1 after ROS activation. It will bind to the nucleus's antioxidant response element (ARE), and increased the expression of peroxidase, such as heme oxygenase-1 (HO-1), glutamate-cysteine ligase catalase (GCLC), glutamate-cysteine ligase (GCLM), and quinone oxidoreductase 1 (NQO1) [22]. ACR treatment could also altered the expression of Nrf2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…The present findings demonstrated that ApoAI MP increased antioxidant properties of PD mouse model by increasing the activities of SOD, CAT and GSH-Px and reducing the content of MDA (Figure 5). During PD, the activities of SOD and the CAT and GSH-Px of the antioxidant defense system are relatively weak, and the improvement of their activities is an important approach in the prevent of PD progression and development (Wang et al, 2018;Chen et al, 2021). Monoamine oxidase promotes the generation of H 2 O 2 , which increases high levels of oxidative stress state and cause injury in PD patients (Youdim, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of CA are well documented, but these effects are generally attributed to the bioactive triterpenes found in the plant (Xu et al, 2012;Zhang et al, 2012). Though the etiology of PD is not exactly figured out, oxidative stress (Trist et al, 2019) and inflammatory responses (Gao et al, 2022) preventing PD advance and development (Wang et al, 2018;Chen et al, 2021). SOD is a strong endogenous antioxidant enzyme for Superoxide radicals.…”
Section: Pretreatmentmentioning
confidence: 99%